Jeden mecz w dwóch odsłonach -język relacji radiowej a telewizyjnej (na przykładzie meczu siatkarskiej Ligi Mistrzów) - Kochmańska, Wioletta (Słowo. Studia językoznawcze, 2012)
In the paper the case of sorts of media’s infiuence language shape of sport’s commentary was brought up led by example of Volleyball Champions League match between Asseco Resovia Rzeszów and Arago de Sete, on 12th December 2012. Records declamations of sports commentators during television coverage and running on the same time radio coverage let to compare the verbal communications exisisting in elements of contents of programs” structure (transmission preceding coverage, relevant coverage and the closure part of coverage) and conclusions of the kind of transmitter’s influence match coverage.